Sex Linkage in Drosophila melanogaster Male Wild Type (N) x Female Miniature (m) Strains - Rasyid, Muh. Anwar; Atika Rahmad, Sintya; Permatasari, Andini; Rivana, Sagita (Rifa'Institute, 2024)
Introduction: The existence of sex links was first discovered by T. H. Morgan and C. B. Bridger in 1910. He found the existence of derivatives that are not in accordance with Mendel's concept. Objective: This study used Drosophila melanogaster with N (wild type) and m (miniature) strains. The crosses performed are N><m and its reciprocal. The results of the cross will be observed regarding the phenotype of the F1 offspring until the resulting F2 is obtained. Method: This research is quantitative descriptive research. Data collection was done by direct observation. The data collected are sex and phenotype of Drosophila melanogaster strain N (normal) and strain m (miniature) for 7 consecutive days. Data analysis used was through comparison of cross reconstruction and chi square test. Result and Discussion: The crossing ratio obtained from the F1 cross N >< m with the result of N and N pups respectively are 1:1 after crossing with each other obtained N, N, m pupswith a ratio of 1.1:1, 8:1 respectively. While the reciprocal of the F1 cross m >< N with N and m pups is 1:1 after crossing each other, we get N, N, m, m pupswith a ratio of 1.2:1, 2:1:1 respectively Conclusions: Sex Linking Phenomenon occurred in F2 of m x N cross